Measurement of Releasing Radon gas at Archaeological Site in Egypt and its Associated Radiation Dose (Journal of Nuclear Technology in Applied Science, 2022)
Radon concentration at Tanis, Sharqai, Egypt, was measured at the site as well as at the laboratory using a sealed Can-technique equipped CR-39 detector which was calibrated in advance. In situ measured radon concentration ranged from 72 ± 9 Bq m-3 to 144 ± 16 Bq m-3, while the equilibrium radon concentration of 20 soil samples collected from the same sites were ranged from 88 ± 12 Bq m-3 to 226 ± 36 Bq m-3 at the laboratory. The average radon concentration is less than the recommended value by ICRP of 300 Bq m-3 but it is higher than the recommended value by WHO of 100 Bq m-3. The radon exhalation rate was ranged from (24 ± 3 to 61 ± 10 10-4) Bq m-2 s-1. It shows a good correlation with the radium content of a linear correlation factor of R = 0.97, which implies, the radium content is a useful index for radon parameters. Moreover, the radiation dose was calculated using radon concentration at sites and its value was ranged from 0.40 ± 0.05 to 0.79 ± 0.09 mSv y-1 for workers and from 0.054 ± 0.007 to 0.108 ± 0.012 mSv y-1 for visitors. From the obtained results, we assure there is no radiation health hazard from visiting the studied archaeological site.
Keywords: Radon; Radiation Dose; Can-technique; Soil; Archaeological Site